An assessment of depression, psychosocial factors, and resilience among women seeking prenatal care at an urban community health center. Issue 2 (18th November 2017) - Johnson, Katherine M.; Paley, Frances M.; Modest, Anna M.; Hacker, Michele R.; Shaughnessy, Sabine; Ricciotti, Hope A.; Scott, Jennifer
Abstract: Objective: To describe the relationship between resilience and mental health and psychosocial characteristics in the prenatal period. Methods: A prospective cohort pilot study was conducted among English‐speaking women aged 18 years or older with singleton pregnancies of at least 20 weeks' duration who received prenatal care at an urban community health center in the USA between March and October 2014. Surveys were administered and a retrospective chart review was conducted. Resilience and depression were measured using validated scales and anxiety was self‐reported. Univariate and bivariate analyses were performed. Results: Thirty women participated. The median resilience score was 82.0 (interquartile range [IQR] 74.0–92.0). Median resilience scores were significantly lower among women with a history of depression (73.0 [IQR 66.0–81.0]) than among those without a history (85.0 [IQR 79.0–92.0]; P= 0.007). A history of using medication for anxiety, depression, or insomnia before pregnancy was also associated with lower resilience (median 74.0 [IQR 64.5–80.0] vs 83.5 [IQR 79.0–92.0]; P= 0.029). Neither anxiety nor substance use was associated with resilience. Higher resilience was associated with religious affiliation and having adequate financial resources (both P< 0.05). Conclusion: Depression history, prior medication use, religious affiliation, and financial security affect resilience in pregnancy. These data inform a strengths‐based approach to prenatal care and future research endeavors. Abstract : Depression history, prior medication use, religious affiliation, and financial security are important variables affecting resilience in pregnancy.